Asas-Asas Perjanjian (Akad), Hukum Kontrak Syariah dalam Penerapan Salam dan Istisna - Ardi, Muhammad (DIKTUM: Jurnal Syariah dan Hukum, 2016)
This paper discusses the basic principles in the agreement (contract) and its application in banking products: salam and istishna. The study concludes that the contract in the perspective of Islam is more known as aqad. While the application of the contract using the contract Salam and Istishna. This contract is a contract of orders and sales. At the end of the contract period runs out, a property of the object becomes the object of such contract.